Long‐term outcome of Wilson's disease complicated by liver disease. Issue 7 (5th June 2021) - Arai, Satoko; Kogiso, Tomomi; Ogasawara, Yuri; Sagawa, Takaomi; Taniai, Makiko; Tokushige, Katsutoshi
Abstract: Background and Aim: Wilson's disease (WD) is a rare inherited disease that causes systemic copper accumulation. This study examined the long‐term course of WD patients with liver disease. Methods: The 12 patients (9 female patients) enrolled in the study had a median age of 28 years (range: 19–57 years) at their first visit to our hospital. Clinical course and fibrosis markers were assessed in all patients. Results: The median age at diagnosis was 24 years (range: 5–42 years). One patient had acute liver failure (ALF) and 11 patients had chronic liver disease (CLD, 5 with cirrhosis). The patients were followed‐up for >20 years. The patient with ALF underwent liver transplantation; the postoperative course during the subsequent 20 years was good. Of the six patients with CLD, liver cirrhosis developed in four patients with interrupted chelating therapy. Two of the patients with cirrhosis died; one of these two patients died at 21 years after liver transplantation. However, the remaining patients with continued treatment exhibited a favorable clinical course for 30 years and none developed hepatocellular carcinoma (HCC). The duration of chelation therapy was significantly negatively correlated ( P  < 0.05) with the fibrosis‐4 index or aspartate aminotransferase to platelet ratio index (APRI) score at the last visit; lower values were indicative of greater treatment success. Patients with an APRI score ≥1.5 had a significantly worse prognosis ( P  < 0.05). Conclusion: Long‐term survival of patients with WD was achieved without worsened liver function or carcinogenesis with appropriate treatment. Treatment disruption should be avoided. Abstract : The duration of chelation therapy for Wilson's disease complicated by liver disease was significantly negatively correlated with the fibrosis‐4 index and aspartate aminotransferase to platelet ratio index (APRI) score at the last visit.